P064 High intestinal Secretory Leukocyte Protease Inhibitor (SLPI) expression correlates with abundant neutrophilic inflammation and identifies Inflammatory Bowel Disease patients with a strong IL-17 response. (30th January 2023) - Nugteren, S; Calado, B; Simons-Oosterhuis, Y; Hulleman-van Haaften, D H; Klomberg, R; Tuk, B; Charrout, M; Lindenbergh-Kortleve, D J; Smits, W K; Doukas, M; Sanders, M A; van Beek, G; et al.
Abstract: Background: Inflammatory bowel disease, comprising Crohn's disease (CD) and ulcerative colitis (UC), is driven by aberrant host-microbial immune interactions. Disease heterogeneity and severity hamper effective treatment, thus new therapeutic strategies tailored to the patient's underlying immune defect are required. In mice, upon epithelial barrier breach and microbiota driven inflammation, colonic intestinal epithelial cells increase Secretory Leukocyte Protease Inhibitor (SLPI) expression. SLPI can exert anti-microbial activity and inhibit NF-kB activation. Therefore, we hypothesized that SLPI expression is increased in the intestine of IBD patients and may differentiate a subgroup of patients with a distinctive underlying immune disease. Methods: Intestinal biopsies and plasma from therapy-naive pediatric patients (age 6-18) with CD (n=41), UC (n=22) or IBD-negative controls (n=15) were collected. Intestinal SLPI protein was detected by immunohistochemistry (IHC), scored semi-quantitatively, and patients were dichotomized into 'SLPI-high' and 'SLPI-low' groups. RNA sequencing and quantitative PCR (qPCR) were performed. Plasma protein concentrations were assessed with Olink technology®. Results: We observed increased SLPI mRNA and protein expression in intestinal tissue of CD and UC patients, compared to IBD-negative controls. Expression was the strongest in macroscopically inflamed tissue and more dominant in colon than in small intestinal ileum. Colonic SLPI expression was associated with endoscopic severity of inflammation, with histologic disease activity, and with clinical disease activity in CD and UC patients. Furthermore, high epithelial SLPI expression associated with abundant neutrophil infiltration and calprotectin expression. RNA-seq revealed that biopsies of SLPI-high patients had a signature of inflammatory neutrophilic inflammation including the genes OSM, IL-1B, and CXCL8, which have been associated with severe disease progression and resistance to anti-TNF treatment. Most notably, biopsies of SLPI-high patients had a signature of increased IL-17 signaling, which was supported by IHC detection of high frequencies of IL-17 producing cells in the paired biopsies and higher plasma concentrations of CCL20, MMP10 and IL-17A. Conclusion: Together, these results demonstrate that intestinal SLPI expression identifies severe IBD patients with high intestinal SLPI expression and immune features of therapy resistance, who have increased IL-17A responses and subsequent neutrophilic inflammation compared to SLPI-low patients. As such, epithelial SLPI expression is a histological parameter that could support tailored treatment strategies in pediatric IBD patients at the time of diagnosis.